Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Changing plans: neural correlates of executive control in monkey and human frontal cortex - Elisa C. Dias; Tammy McGinnis; John F. Smiley; John J. Foxe; Charles E. Schroeder; Daniel C. Javitt (Experimental Brain Research, 2006)